2014
DOI: 10.1007/s11552-014-9727-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Ulnar Shortening Osteotomy: An Institutional Review

Abstract: General outcome measures were favorable. Smokers and patients with workers' compensation claims experienced significantly poorer outcomes. However, the incidence of nonunion and delayed union was higher than most reports in the literature. Furthermore, we demonstrated a high refracture rate (11.4 %) following removal of hardware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
25
0
2
Order By: Relevance
“…16,23,24,27 Conversely, Rajgopal et al reported that more than 20% of patients had delayed union or nonunion and that 45% required hardware removal because of plate irritation. 37 Chan et al also noted a high risk of plate irritation (51%). 38 These high complication rates of USO can support our recommendation that USO can be used only for recalcitrant cases after arthroscopic debridement.…”
Section: Discussionmentioning
confidence: 97%
“…16,23,24,27 Conversely, Rajgopal et al reported that more than 20% of patients had delayed union or nonunion and that 45% required hardware removal because of plate irritation. 37 Chan et al also noted a high risk of plate irritation (51%). 38 These high complication rates of USO can support our recommendation that USO can be used only for recalcitrant cases after arthroscopic debridement.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11] Small changes in ulnar variance create significant changes in force transmission through the ulnocarpal joint. 12 Classically, diaphyseal osteotomy has demonstrated encouraging short-and midterm results [13][14][15][16][17] but several complications have been reported with this technique, including residual ulnar positive variance, 17 hardware prominence requiring removal, [18][19][20][21] delayed union or nonunion, [22][23][24][25] and complex regional pain syndrome. 25,26 More recently, distal metaphyseal ulnar-shortening osteotomy has been reported in several studies with promising results.…”
mentioning
confidence: 99%
“…12 Classically, diaphyseal osteotomy has demonstrated encouraging short-and midterm results [13][14][15][16][17] but several complications have been reported with this technique, including residual ulnar positive variance, 17 hardware prominence requiring removal, [18][19][20][21] delayed union or nonunion, [22][23][24][25] and complex regional pain syndrome. 25,26 More recently, distal metaphyseal ulnar-shortening osteotomy has been reported in several studies with promising results. [27][28][29][30] Metaphyseal cancellous bone has richer blood supply and is less resistant to osteotomy compared with diaphyseal bone.…”
mentioning
confidence: 99%
“…In our study, three patients (19%) requested removal of metalwork due to irritation. This is better than most studies that have rates of 30 to 79%, 5,6,12,16,17,22 but not as good as two studies with rates of 0 13 and 7%. 10 However, these studies included a variety of USO plating systems, so new, lower profile USO plates may decrease the irritation and need for metalwork removal.…”
Section: Discussionmentioning
confidence: 52%